2023
DOI: 10.3389/fpls.2023.1285547
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics profiling revealed multi-stress responsive roles of the CC-NBS-LRR genes in three mango cultivars

Muhammad Tahir ul Qamar,
Muhammad Sadaqat,
Xi-Tong Zhu
et al.

Abstract: The nucleotide-binding site-leucine-rich repeat (NBS–LRR) gene family is the largest group of disease resistance (R) genes in plants and is active in response to viruses, bacteria, and fungi usually involved in effector-triggered immunity (ETI). Pangenome-wide studies allow researchers to analyze the genetic diversity of multiple species or their members simultaneously, providing a comprehensive understanding of the evolutionary relationships and diversity present among them. The draft pan-genome of three Mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The chromosomal positions of each Pyrus PAOs were extracted from GFF/GFF3 files and mapped to chromosomes using TBtools-II v2.067: Gene Location Visualize advanced (C. Chen et al, 2018 ). By assessing whether the shorter gene’s length covered 70% of the longer gene and if the alignment similarity between the two genes was 70% or higher, instances of PAOs gene duplication were identified ( ul Qamar et al, 2023 ). The duplication pattern, whether segmental or tandem, was also examined.…”
Section: Methodsmentioning
confidence: 99%
“…The chromosomal positions of each Pyrus PAOs were extracted from GFF/GFF3 files and mapped to chromosomes using TBtools-II v2.067: Gene Location Visualize advanced (C. Chen et al, 2018 ). By assessing whether the shorter gene’s length covered 70% of the longer gene and if the alignment similarity between the two genes was 70% or higher, instances of PAOs gene duplication were identified ( ul Qamar et al, 2023 ). The duplication pattern, whether segmental or tandem, was also examined.…”
Section: Methodsmentioning
confidence: 99%
“…The chromosomal positions for each Pyrus TIR1/AFB were retrieved from the GFF/GFF3 files and mapped to chromosomes by using the gene location visualization tool of the TBtools software (Chen et al, 2018). Depending on whether the shorter gene's length covered 70% of the longer gene and whether the two aligned genes' similarity was equal to or greater than 70%, TIR1/ AFB gene duplication occurrences were identified (Tahir ul Qamar et al, 2023). The genes were also checked to determine whether the duplication pattern was segmental or tandem.…”
Section: Chromosomal Distribution Ka/ks Rate and Gene Duplication Ana...mentioning
confidence: 99%
“… Liu et al, 2021 ) , 361 in Solanum tuberosum ( Jupe et al, 2012 ) , 78 in Solanum pimpinellifolium ( Wei et al, 2020 ) , 14 in Lagenaria siceraria, 146 in Triticum urartu ( Qian et al, 2021 ) , 166 in Discorea rotundata, 103 in Glycine max ( Afzal et al, 2022 ), 467 in Hordeum vulgare ( Liu et al, 2017 ), 54 in Broussonetia papyrifera (X. Zhang et al, 2023 ), 95 in Elaeis guineensis ( Rosli et al, 2018 ) , 10 in Citrus sinensis ( Yin et al, 2023 ), 47 in Alphonso , 27 in Hong Xiang Ya , and 36 in Tommy atkins ( ul Qamar et al, 2023 ). Machine learning approaches have also been applied in studies reported previously for the elucidation of candidate genes implicated in multi-stress responsiveness in Oryza sativa and Sorghum bicolor ( Woldesemayat et al, 2018 ; Ramkumar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%